MANAJEMEN PENGEMBANGAN DIRI GURU FISIKA DI SMA NEGERI 8 PEKANBARU - SOVIETI SOVIETI; MUHAMMAD NASIR; MARZUKI MARZUKI (Universitas Riau, 2017)
This study aimed to describe the self-development management of Physicsteachers of SMAN 8 Pekanbaru. The study employed the descriptive method and the datawere collected by way of observation, interview and documentation. The data were obtainedfrom Physics teachers of SMAN 8 Pekanbaru that were accordingly analyzed through datagathering, data reduction, data display and conclusion drawing. The findings of the researchindicated that (1) SMAN 8 Physics teachers were developing positively where they alwaystried to upgrade themselves and had positive commitment in order that the students lovedPhysics subject; (2) SMAN 8 Physics teachers always developed themselves in order todevelop the science of Physics they possessed; (3) The focus of self-development of SMAN8 Physics teachers was not satisfaction; (4) SMAN 8 Physics teachers never felt satisfiedwith the achievement they achieved; (5) SMAN 8 Physics teachers kept their principle tokeep on learning; (7) SMAN 8 Physics teachers were always committed to being disciplinethemselves and being discipline with the time either in class or out of class so that they couldbecome examples to their students; (8) SMAN 8 Physics teachers were committed to applyingthe knowledge they have obtained from books, seminars, trainings and from the SubjectTeachers Discussion program (MGMP). With the research findings it is expected that SMAN8 Physics teachers could possess high motivation in teaching and that the students could alsobe highly motivated and have better learning achievement.